2007
DOI: 10.1111/j.1464-410x.2007.07284.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the internal pudendal artery as a congenital contributing factor to age at onset of erectile dysfunction in Japanese

Abstract: basic type), in which the internal pudendal artery (IPA) originates from the anterior trunk at the level between the linea terminalis and the major ischial notch; Type 2, the IPA originates from the anterior trunk of the IIA at the level of the major ischial notch or more distally; Type 3, the IPA originates directly from the IIA at a level proximal to the linea terminalis; Type 4, the IPA originates together with the superior and inferior gluteal artery within 1 cm of each other; and Type 5, the penile blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…, 2005) some patients with severe CAD still report normal erectile function. Interestingly, recently Kawanishi et al. (2008) demonstrated that congenital vascular abnormalities could explain, at least partially, this apparent incongruence.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2005) some patients with severe CAD still report normal erectile function. Interestingly, recently Kawanishi et al. (2008) demonstrated that congenital vascular abnormalities could explain, at least partially, this apparent incongruence.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Finally, it should be recognized that although the prevalence of ED in subjects with CAD is quite high (Montorsi et al, 2005) some patients with severe CAD still report normal erectile function. Interestingly, recently Kawanishi et al (2008) demonstrated that congenital vascular abnormalities could explain, at least partially, this apparent incongruence.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Kawanishi et al. [1]. reported this retrospective radiological study examining the effect of different anatomical variations of the internal pudendal artery on the development of erectile dysfunction (ED) in young or older patients.…”
mentioning
confidence: 99%
“…In our studies we mainly focused on the dorsal nerve of penis, but paper of Kawanishi et al. [1], on the current knowledge of clinical anatomy of the subpubic region, lead me to the conclusion that it might be very interesting to study anatomical variations of the penile‐supplying arteries in the subpubic region.…”
mentioning
confidence: 99%
See 1 more Smart Citation